Dialogue of Cultures in the Poetics of Veronika Dolina - Mnich, Ludmiła (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The article deals with various types of dialogue of cultures in the songs by Veronika Dolina. The genre of author song (Russian and Soviet singer-songwriters’ works) is analysed as a special kind of dialogue with listeners as well as with history and culture. In particular, the author interprets and places in intertextual context three songs by Dolina: ‘The Aunt Told Me’, ‘On the Death of A. D. S.’ and ,The Cardinal Is Still Young’.